Proximate analysis and oxidative stability of wax from the nuts of Krabok (Irvingia malayana) - P. Sirisa-Ard (2018)
Proximate analysis and oxidative stability of Krabok nuts were carried out in order to obtain more extensive information pertaining to their suitability as the raw material for a food supplement. It was found that 100 g of the nuts consist of 1.79 g of ash, 2.08 g of moisture content, 66.78 g of crude fat, 9.07 g of total carbohydrate, 3.40 g of crude protein, 61.43 mg of iron and 103.30 mg of calcium. The oxidative stability of the nuts was studied during storage at four different conditions including 4°C, 45°C, room temperature (23-25°C) and sun light exposure. Peroxide values were measured every 30 days for 4 months. At 45°C, the peroxide values were found in the range 2.31-3.94 meq ROOH/kg of fat, which is higher than at other conditions. The nuts stored at 4°C showed the lowest peroxide value, ranging from 1.37 to 2.70 meq ROOH/kg of wax. Where as, they were 1.1446-1.1877 meq ROOH/kg of fat at room temperature. It was concluded that the preferred temperature for keeping the nuts is at 4°C. © ISHS.